Semantic segmentation with attention dense U-net for lung extraction from X-ray images - Auvy, Akib Al Mahmud; Sharif, Shezhan; Chowdhury, Aseer Iqtider; Elahi, Mahbub-E; Mahmud, Washik Al (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.